Ganglioside GM2-activator protein and vesicular transport in collecting duct intercalated cells - Mundel, Thomas; Heid, Hans; Kriz, Wilhelm; Mundel, Peter (Journal of the American Society of Nephrology, 1999)
Abstract. This study describes the molecular characterization of an antigen defined by an autoantibody from a woman with habitual abortion as GM2-activator protein. The patient showed no disorder of renal function. Accidentally with routine serum screening for autoantibodies, an immunoreactivity was found in kidney collecting duct intercalated cells. Three distinct patterns of immunostaining of intercalated cells were observed: staining of the apical pole, basolateral pole, and diffuse cytoplasmic labeling. Ultrastructurally, the immunoreactivity was associated with “studs,” which represent the cytoplasmic domain of the vacuolar proton pump in intercalated cells. This pump is subjected to a shuttling mechanism from cytoplasmic stores to the cell membrane, which exclusively occurs in intercalated cells. Peptide sequences of a 23-kD protein purified from rat kidney cortex showed complete identity with corresponding sequences of GM2-activator protein. In the brain, GM2-activator protein is required for hexosaminidase A to split a sugar from ganglioside GM2. Because neither ganglioside GM2 nor GM1 (its precursor) is present in significant amounts in the kidney, the previous finding that this tissue contains the highest level of activator protein in the body was confusing. In this study, a novel role for GM2-activator protein in intercalated cells is proposed, and possible roles in the shuttling mechanism are discussed.
Gesehen am 08.09.2017